Pengaruh Kualitas Layanan Terhadap Kepuasan, Kepercayaan dan Loyalitas Pelanggan Pada E-Commerce (Studi Kasus : Berrybenka) - Rika Mardatilla; Ari Kusyanti; Himawat Aryadita (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
E-commerce is one of the development of technology that is very influential in business field where companies are required to have an innovation in online transaction. The advantages of e-commerce can be experienced by both the sellers and cutomers as the customers get the things that they want easily without spending much time and effort. On the other hand, the sellers can also expand their market share quickly. One of the companies that utilizes the sopistication of the technology in Indonesia is Berrybenka.Berrybenka is a fashion e-commerce in Indonesia that is quite popular nowdays. However, at this time there is not yet known who the effect of service quality that can affect customer satisfaction, trust and loyalty to Berrybenka. This research model built on the quality of service will be five dimensions namely, ease of use, web design, responsive, personalization, assurance that affect satisfaction, trust, customer loyalty based on previous research. The completed data were analyzed by using structural equation modeling (SEM). The results of this study indicate that the five dimensional service quality does not affect satisfaction, satisfaction take affect positive and signification trust, and word-of-mounth, but does not affect intention, trust take affect positive and signification intention-mounth, but does not affect word-of-mounth, and customer loyalty will be two dimensions namely, word-of-mounth take affect and signification intention.